Optimalisasi Digital Learning Pada Diskusi Kolaboratif Mata Kuliah Agama Islam - Atikoh, Nurul; Susilo, Suko (JOM, 2025)
The development of digital technology today encourages innovation in learning, including in Islamic Religion courses. Digital learning and collaborative discussion methods are considered to increase student understanding and active involvement, especially in a university environment that has distance learning needs such as PSDKU Brawijaya University Kediri. However, optimizing this method is still a challenge due to the diverse backgrounds of students. This research aims to optimize the application of digital learning in collaborative discussion method in Islamic Religion course. Another objective is to evaluate the effectiveness of this learning model in improving students' understanding and active participation. This research uses qualitative method with case study approach. Data were collected through classroom observation, interviews with lecturers and students, and analysis of the results of collaborative discussion assignments. The results showed that the integration of various digital applications such as Wordwall, Canva, Quizizz, PowerPoint, YouTube, and Spin Wheel successfully increased student participation and engagement in the learning process. These applications not only facilitate interaction between students but also encourage the development of a deeper understanding of the material with interactive and engaging learning methods. Wordwall and Quizizz proved effective in providing a quiz experience that supports gamification-based learning, while Canva and PowerPoint were used to enrich the visual material so that it is easier to understand. The use of YouTube as an audio-visual medium supports students' in-depth understanding of concepts, while Spin Wheel adds an element of engagement in randomized question and answer sessions, making the classroom atmosphere more dynamic. This approach shows that the application of digital media in collaborative discussions has great potential to improve the quality of learning, especially in courses that require understanding of concepts and values such as Islamic Religion.